6(x+3)=27

Simple and best practice solution for 6(x+3)=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x+3)=27 equation:


Simplifying
6(x + 3) = 27

Reorder the terms:
6(3 + x) = 27
(3 * 6 + x * 6) = 27
(18 + 6x) = 27

Solving
18 + 6x = 27

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + 6x = 27 + -18

Combine like terms: 18 + -18 = 0
0 + 6x = 27 + -18
6x = 27 + -18

Combine like terms: 27 + -18 = 9
6x = 9

Divide each side by '6'.
x = 1.5

Simplifying
x = 1.5

See similar equations:

| 16m^2-88m+40=0 | | -31-4x=-55(1+5x) | | 16t^2=323 | | 17-z=13 | | 6p=208 | | 16t^2=223 | | 9[2-2x]=3x+2 | | 3y+20= | | (3x+10)=5x | | 15+7x-2x^2= | | 10x^3+12x^2+2x= | | 11x^2+x^3=0 | | 16t^2=338 | | 2x-45+1x+30=180 | | 2x^2+7x+15= | | 8n-7(n-8)=32+5n | | -10n+151=-589 | | 5b+14=-2(2-4b) | | (4h-2)=2(h+3) | | 8(v-8)=-8v-16 | | 44x-29=37x-15 | | 1-5x+3x+4=-3(x+8)+2(6x-2) | | 3+6n-7n=0 | | 2n+6=-20 | | 8s-[8+6s]=20 | | 2y+2y-3+3-7=42 | | 9(d+640)=522 | | (2-1)m=-3 | | 2-7(3v+7)=-131 | | 2x-2+6x=2(x+8) | | -2(x+5)=5x+39 | | 2a^2=20a-32 |

Equations solver categories